Analisis Dramaturgi Kaum Gay Kota Bengkulu - Ardila, Windi; Gushevinalti, Gushevinalti; Firmansyah, Mas Agus (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research uses quantitative theoretical methods from Ervin Goffman, namely the theory of dramaturgical analysis (Impression Management), a dramaturgical study approach. Gay dramaturgy requires an area called a stage as a place for actors to play their functions and roles so that they can be seen by the audience. Front stage or front stage and back stage or back stage which is a place for gay individuals to build interactions with their social environment. The front stage of Gay people is divided into two, namely their home or family environment and the community environment. Based on the situation that the author found in the interview and observation process, it can be concluded that gay people also need a place where they can relax with the people around them without having to pretend and can be completely themselves as gay people. So this back stage was created which is a private stage for gay people to interact with their fellow gay friends.